Prevalence of Multidrug Resistance and Extended-Spectrum β-Lactamase Carriage of Clinical Uropathogenic Escherichia coli Isolates in Riyadh, Saudi Arabia - Abdulaziz Alqasim; Ahmad Abu Jaffal; Abdullah A. Alyousef (International Journal of Microbiology)
The prevalence of extended-spectrum β-lactamase-producing Escherichia coli (ESBL-producing E. coli) has recently increased worldwide. This study aims at determining the antimicrobial susceptibility patterns of a collection of clinical E. coli urine isolates and evaluating the ESBL carriage of these isolates at phenotypic and genotypic levels. A total of 100 E. coli urine isolates were collected at a tertiary healthcare centre in Riyadh from January 2018 to March 2018. Antimicrobial susceptibility testing was carried out for all isolates. ESBL production was characterized at phenotypic and genotypic levels using double-disc synergy test and polymerase chain reaction, respectively. Detection of different ESBL variants was performed using DNA sequencing. Of 100 E. coli isolates, 67 were associated with multidrug resistance (MDR) phenotype. All isolates showed variable resistance levels to all antibiotics used here expect to imipenem, where they were all imipenem-sensitive. 33 out of 100 E. coli isolates were positive for ESBLs by phenotypic and genotypic methods. Among all ESBL-positive E. coli isolates, the CTX-M was the most prevalent ESBL type (31/33 isolates; 93.94%). CTX-M-15 variant was detected in all isolates associated with CTX-M carriage. Multiple ESBL gene carriage was detected in 15/33 isolates (45.45%), where 11 (33.33%) isolates produced two different ESBL types while 4 isolates (12.12%) associated with carrying three different ESBL types. Our study documented the high antimicrobial resistance of ESBL-producing E. coli to many front-line antibiotics currently used to treat UTI patients, and this implies the need to continuously revise the local guidelines used for optimal empirical therapy for UTI patients. It also showed the high prevalence of ESBL carriage in E. coli urine isolates, with CTX-M-15 being the most predominant CTX-M variant.